2017
DOI: 10.1051/itmconf/20171101011
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective Virtual Machine Placement for Load Balancing

Abstract: Abstract. The virtual machine placement is closely related to the efficient and balanced utilization of physical resources. In this paper, the influence of two scenarios about resource utilization on load balancing is analyzed. A multi-objective ant colony optimization algorithm is proposed to solve the virtual machine placement problem, which balances the load among physical machines and the internal load of physical machine simultaneously. The proposed algorithm is compared with two single objective ant colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The MBBO/DE algorithm offers better results than the ACO algorithm and the genetic algorithm [33]. As can be seen in Table 1, the MOACO algorithm provides better results than ACO, first fit (FF) and greedy scheduling (GS) algorithms [34]. From the comparison shown in Table 2, it can be concluded that the LBA-HB algorithm is more efficient than round robin, modified throttled, ACO, artificial bee colony (ABC) and honey bee [32].…”
Section: Comparison and Analysis Of Optimization Algorithmsmentioning
confidence: 98%
See 1 more Smart Citation
“…The MBBO/DE algorithm offers better results than the ACO algorithm and the genetic algorithm [33]. As can be seen in Table 1, the MOACO algorithm provides better results than ACO, first fit (FF) and greedy scheduling (GS) algorithms [34]. From the comparison shown in Table 2, it can be concluded that the LBA-HB algorithm is more efficient than round robin, modified throttled, ACO, artificial bee colony (ABC) and honey bee [32].…”
Section: Comparison and Analysis Of Optimization Algorithmsmentioning
confidence: 98%
“…• For load balancing, MBBO/DE algorithm provides same results as ACO algorithm in scenario 1, • Migration time is longer than in other algorithms simulated in scenario 2. MOACO algorithm Multi-objective virtual machine placement for load balancing [34].…”
Section: Moo Algorithmmentioning
confidence: 99%
“…Modern cloud systems have numerous open research challenges including resource management, load balancing, security, privacy, and multi‐clouds 16–22. In this section, the recent works on load balancing are summarized as this study concentrates on multi‐objective load balancing.…”
Section: Related Workmentioning
confidence: 99%
“…VM placement approaches can be classified based on the number of objectives being optimized and the optimization scheme being used. Based on the number of objectives, these algorithms can be classified into single‐objective and multi‐objective solutions 16,22,24. Furthermore, VM placement schemes can be classified into mono‐objective, multi‐objective as mono‐objective (MAM), and true multi‐objective approaches based on the optimization scheme employed 25.…”
Section: Related Workmentioning
confidence: 99%
“…Here, u c ¯ , u m ¯ , and u b ¯ represent the average utilization rates of CPU, memory, and bandwidth of all PMs, respectively. In a similar work, Fang and Qu 14 propose a metric called outer load balancing degree (OBD) to reflect the degree of load balancing among the PMs. Gao et al 15 propose a resource wastage model to minimize the total resource wastage and fully utilize multidimensional resources.…”
Section: Modeling and Formulationmentioning
confidence: 99%